Transcription of the Recorded Oral Interview with Mrs. Nebolisa - Oloko, Patrick; Kibora, Ludovic (Rethinking the "Informal" and Mainstreaming African Popular Arts and Entertainment, 2021)
Transcription of the recorded oral interview with Mrs. Nebolisa of Rethinking the Informal and Mainstreaming African Popular Arts and Entertainment
Keywords: Arts; Aesthetics; Music; Scholars; African Studies; Popular Music Studies; African Music; Cultural Economy